Yellow Beach 2 after 75 years : the archaeology of a WWII invasion beach on Saipan and its historic context in the Commonwealth of the Northern Mariana Islands - Dixon, Boyd, (Access archaeology., 2019)
On June 15, 1944, Afetna Point was called 'Yellow Beach 2' by the U.S. Marines and Army infantry braving Japanese resistence to establish a beachhead before capturing As Lito airfield the following days. After 75 years, this story presents archaeological evidence, archival records, and respected elders' accounts from WWII.